Prazosin + naltrexone decreases alcohol drinking more effectively than does either drug alone in P rats with a protracted history of extensive voluntary alcohol drinking, dependence and multiple withdrawals - Rasmussen, Dennis D (Alcohol Clin Exp Res, 2015)
BACKGROUND: Prazosin (PRZ, an α(1)-adrenergic receptor antagonist) and naltrexone (NTX, a non-specific opioid receptor antagonist) each decrease alcohol drinking when administered to rats selectively-bred for high voluntary alcohol drinking (alcohol-preferring, or “P”), and the combination of PRZ+NTX decreases alcohol drinking more effectively than does either drug alone. Since drug responsiveness can depend on history of alcohol drinking and dependence, we investigated whether various schedules of PRZ and NTX administration, alone or in combination, are effective in decreasing alcohol drinking in male P rats with a history of protracted voluntary alcohol drinking, dependence and repeated withdrawals closely resembling human alcoholism. METHODS: Male P rats became alcohol-dependent during 1 year of ad libitum 24 h/day access to food, water and 20% alcohol with repetitive temporary alcohol withdrawals. Four sequential studies then addressed effects of oral PRZ (2 mg/kg) and NTX (10 mg/kg), alone or together, on alcohol drinking during: 1) daily alcohol access with daily drug treatment, 2) intermittent alcohol access with daily drug treatment, 3) intermittent alcohol access with occasional drug treatment, and 4) post-deprivation reinstatement of alcohol access. RESULTS: The combination of PRZ+NTX consistently suppressed alcohol drinking during daily or intermittent alcohol access conditions and when drug treatment was either daily or occasional. PRZ+NTX was consistently more effective than either drug alone. The reduction in alcohol drinking was not due to sedation, motor effects or malaise. CONCLUSIONS: Both daily and “as-needed” treatment with PRZ+NTX are highly effective in suppressing daily, intermittent and post-deprivation alcohol drinking in male P rats with a protracted history of alcohol dependence and repeated withdrawals. This drug combination may be especially effective for treating individuals with long histories of heavy alcohol abuse, dependence and repeated relapse, as commonly encountered in clinical practice.